2006
DOI: 10.1021/jp062859u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Hyperpolarizability Components of Hemicyanine Dyes by Measuring the Anisotropic Fluorescence and Second Harmonic of the Dyes Uniformly Aligned within Zeolite Channels

Abstract: A unidirectional ensemble of hemicyanine molecules was prepared by inserting the molecules into the vertical channels of a uniformly oriented zeolite (silicalite-1) film grown on a glass substrate. Fluorescence from this sample excited with light polarized along the vertical channel was 50 times larger than that excited with light polarized orthogonal to the vertical channel direction. These vertically aligned hemicyanine dyes were used to determine the ratio of the molecular hyperpolarizability components zxx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…That DAMPI effectively adsorbs in the pores of the zeolite is further supported by the observation that 2 h is needed to obtain equilibrium because diffusion of the large dye molecules in the narrow 10-membered rings of the MFI zeolite is expected to be slow. In addition, it has been shown that hemicyanine dyes adsorb in the straight pores of silicalite-1 from the liquid phase. ,, In the latter case, it has been shown that adsorption needs 4 h to be completed in methanol, which is similar to the time observed here for DAMPI adsorption . Finally, in previous studies, for the inclusion of a hemicyanine dye in the straight channels of a b-oriented silicalite-1 film, an apparent tilt angle of 11.3° instead of 0° was determined by fluoresence spectroscopy at an angle of 7.7° instead of 0° by SHG. , …”
supporting
confidence: 75%
See 1 more Smart Citation
“…That DAMPI effectively adsorbs in the pores of the zeolite is further supported by the observation that 2 h is needed to obtain equilibrium because diffusion of the large dye molecules in the narrow 10-membered rings of the MFI zeolite is expected to be slow. In addition, it has been shown that hemicyanine dyes adsorb in the straight pores of silicalite-1 from the liquid phase. ,, In the latter case, it has been shown that adsorption needs 4 h to be completed in methanol, which is similar to the time observed here for DAMPI adsorption . Finally, in previous studies, for the inclusion of a hemicyanine dye in the straight channels of a b-oriented silicalite-1 film, an apparent tilt angle of 11.3° instead of 0° was determined by fluoresence spectroscopy at an angle of 7.7° instead of 0° by SHG. , …”
supporting
confidence: 75%
“…Hemicyanine dyes such as DAMPI have one dominant second-order nonlinear polarizability β zzz with z along the long molecular axis . The hyperpolarizability β zzz can be related by a coordinate transformation to the different elements of χ (2) ads in the laboratory coordinates ( X , Y , Z ) (Scheme ).…”
mentioning
confidence: 99%
“…This model has proven to be useful for the description of a variety of dye-zeolite composites. , It does not include, however, the possibility of a degree of disorder in the orientational behavior of the dyes, due to either time or spatial fluctuations. An alternative approach has been introduced considering that the molecules lie within a filled cone distribution along the c -axis, to understand nonlinear optical properties of aligned zeolite crystals. , This model however assumes a complete angular disorder within the cone angular aperture, which is not expected for a large variety of inserted molecules. At last, both approaches require that the distribution exhibits a cylindrical symmetry along the crystal c -axis, which is not the case if possible local defects induce a misorientation of the cone axis.…”
Section: Introductionmentioning
confidence: 99%
“…This surface selection process was later confirmed by pyro-electric microscopy measurements [16]. In fact the surface selection process seems quite general as the SHG activity of zeolites filled with aromatic molecules with different positions for the substituents and diverse functional groups such as alcohols, dimethylamino, nitrile, alkyl and carboxylic acid groups has been reported [9,[17][18][19][20][21]. There are however exceptions: p-nitroaniline adsorbed in the one-dimensional 10-ring pores of ZSM-12 did not show any SHG activity [22].…”
Section: Zeolites As Nlo Materialsmentioning
confidence: 67%
“…There are however exceptions: p-nitroaniline adsorbed in the one-dimensional 10-ring pores of ZSM-12 did not show any SHG activity [22]. Apart from the traditional Kurtz powder measurements (see Section 4) [17], also polarization dependent measurements on single zeolite crystals [18,19] and oriented zeolite films [9,20,21] were performed, confirming the alignment of the adsorbed molecules along the pore direction. Similarly spectral and polarization dependent SHG measurements were done on single walled carbon nanotubes (SWCNT) inside AlPO 4 -5 single crystals to confirm that they are chiral (4,2) SWCNTs [23].…”
Section: Zeolites As Nlo Materialsmentioning
confidence: 73%